Antisense oligonucleotide therapeutics in clinical trials for the treatment of inherited retinal diseases - Xue, K; MacLaren, RE (Taylor and Francis, 2020)
Introduction Antisense oligonucleotides (ASOs) represent a class of drugs which can be rationally designed to complement the coding or non-coding regions of target RNA transcripts. They could modulate pre-messenger RNA splicing, induce mRNA knockdown, or block translation of disease-causing genes, thereby slowing disease progression. The pharmacokinetics of intravitreal delivery may enable ASOs to be effective in the treatment of inherited retinal diseases. Areas covered We review the current status of clinical trials of ASO therapies for inherited retinal diseases, which have demonstrated safety, viable durability, and early efficacy. Future applications are discussed in the context of alternative genetic approaches, including gene augmentation and gene editing. Expert opinion Early efficacy data suggest that the splicing-modulating ASO, sepofarsen, is a promising treatment for Leber congenital amaurosis associated with the common c.2991+1655A>G mutation in CEP290. However, potential variability in clinical response to ASO-mediated correction of splicing defect on one allele in patients who are compound heterozygotes needs to be assessed. ASOs hold great therapeutic potential for numerous other inherited retinal diseases with common deep-intronic and dominant gain-of-function mutations. These would complement viral vector-mediated gene augmentation which is generally limited by the size of the transgene and to the treatment of recessive diseases.